2016
DOI: 10.1080/1828051x.2016.1239511
|View full text |Cite
|
Sign up to set email alerts
|

Role of coenzyme Q and vitamin E on stallion semen motility evaluated both in frozen and cooled-stored semen

Abstract: Several studies reveal that coenzyme Q (CoQ) and vitamin E (Vit. E) act against oxidative deterioration, and that CoQ restores the active and antioxidant form of Vit. E. These two antioxidants, acting against lipid peroxidation, seem to be able to improve motility parameters of spermatozoa. The objective of this study is to evaluate the addition of CoQ and Vit. E to semen extender for equine spermatozoa in order to evaluate possible effects on semen motility. First, immediately after collection, semen samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The CoQ10 is present at high levels in the spermatozoon as its reduced form, ubiquinol [32,33]. It has been successfully used for freezing stallion semen with contrasting results [34][35][36][37], whereas other authors showed that adding it to the horse-sperm freezing medium did not increase sperm motility [38]. In humans, CoQ10 has been used in the semen of oligospermic patients successfully reducing the number of reactive oxygen species and decreasing sperm damage during cryopreservation [39].…”
Section: Introductionmentioning
confidence: 99%
“…The CoQ10 is present at high levels in the spermatozoon as its reduced form, ubiquinol [32,33]. It has been successfully used for freezing stallion semen with contrasting results [34][35][36][37], whereas other authors showed that adding it to the horse-sperm freezing medium did not increase sperm motility [38]. In humans, CoQ10 has been used in the semen of oligospermic patients successfully reducing the number of reactive oxygen species and decreasing sperm damage during cryopreservation [39].…”
Section: Introductionmentioning
confidence: 99%
“…In sperm cells, the defence mechanism against lipid peroxidation also involves non-enzymatic molecules such as thioredoxin and glutathione, thiol-containing molecules, and vitamins E, C, and D ( 42 ). For human and several mammalian species sperm, the freezing medium has been supplemented with low-molecular-weight antioxidants to reduce oxidative stress ( 16 , 17 , 23 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Each ejaculates were divided into three treatments, being control (extender BotuCrio® -Botupharma, Botucatu, SP, Brazil) and the same extender with two different concentrations of CoQ-10 (Sigma-Aldrich® -C9538) that were added (50 µmol of CoQ-10 and 1 mmol of CoQ-10) (Figure 1). These two chosen concentrations of CoQ-10 were based on literature review, especially in papers (Lewin and Lavon, 1997;Rossi et al, 2016). Hence, the treatments were denominated as control (CONT), 50 µmol CoQ-10 and 1 mmol CoQ-10.…”
Section: Extender Treatmentsmentioning
confidence: 99%